2013
DOI: 10.1038/ejcn.2013.202
|View full text |Cite
|
Sign up to set email alerts
|

Higher insulin sensitivity in vegans is not associated with higher mitochondrial density

Abstract: Vegans have a higher IS, but comparable mitochondrial density and IMCL content with omnivores. This suggests that a decrease in whole-body glucose disposal may precede muscle lipid accumulation and mitochondrial dysfunction in IR development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We observed that the 5% and 10% fresh pollen refeeding diet triggered an increase in CS activity in the plantaris muscle of food-restricted old rats. CS is a key enzyme of the Krebs cycle, and beside its functional importance for mitochondria, CS activity also is an index of mitochondrial density [ 26 , 56 ]. Thus, refeeding with fresh pollen-containing diets appeared to increase mitochondrial biogenesis in old malnourished rats.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the 5% and 10% fresh pollen refeeding diet triggered an increase in CS activity in the plantaris muscle of food-restricted old rats. CS is a key enzyme of the Krebs cycle, and beside its functional importance for mitochondria, CS activity also is an index of mitochondrial density [ 26 , 56 ]. Thus, refeeding with fresh pollen-containing diets appeared to increase mitochondrial biogenesis in old malnourished rats.…”
Section: Discussionmentioning
confidence: 99%
“…Medical records of the out-patient department at a tertiary clinical nutrition center (University Hospital Kralovske Vinohrady, Prague, Czech Republic) were used for the present study. Data of vegan adults, who attended medical check-ups between 2012 and 2019, and volunteers from previous studies [9,10] of the department, who self-identified themselves as vegans (exclusive plant-based diet) were analyzed (n = 151). Non-vegan healthy volunteers, who were recruited for previous research projects of the department (Czech Rep. Ministry of Health grants 14,416 and 18-01-00040; Charles University grant 1,280,218), were used as controls subjects.…”
Section: Study Populationmentioning
confidence: 99%
“…Numerous comparative studies reveal no fundamental differences in morphological or enzymatic equipment of skeletal muscle in vegetarians/vegans compared to omnivores [14,15]. In our study, we showed that visceral fat decreased more in V compared to C [3].…”
Section: Discussionmentioning
confidence: 39%